Accelerated skin wound healing using electrospun nanofibrous mats blended with mussel adhesive protein and polycaprolactone. Issue 1 (11th October 2016) - Kim, Bum Jin; Cheong, Hogyun; Choi, Eun‐Som; Yun, So‐Hee; Choi, Bong‐Hyuk; Park, Ki‐Soo; Kim, Ick Soo; Park, Dae‐Hwan; Cha, Hyung Joon
Abstract: Nanofibrous scaffolds have been assessed as one of many promising tissue engineering scaffolds to be utilized for wound‐healing applications. Previously, we reported multi‐functionalized electrospun nanofibrous scaffolds blended with mussel adhesive protein (MAP) and polycaprolactone (PCL), which provide durable mechanical strength, cell‐friendly environments, and a substantial ability to capture diverse bioactive molecules without any surface modifications. In the present work, we applied the blended nanofibrous mats of MAP and PCL for in vivo skin wound healing. The nanofibrous mats showed accelerated regeneration in a rat skin wound‐healing model, which might be attributed to a highly compatible environment for keratinocyte cell growth, an ability to capture inherent growth factors, and an efficient exudate absorption capacity. Thus, this work would suggest that adhesive property of scaffold could be a factor of successful application for wound healing. The MAP‐blended nanofibers could also be potentially exploited for diverse tissue regeneration applications. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 218–225, 2017.